Dissipation Behavior of Fenpyroximate Residues in Black Tea and Brew - Subbiah Seenivasan; Narayanan Nair Muraleedharan (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2015)
Fenpyroximate is an effective acaricide on several food crops. In the present study, dissipation of residue of this acaricide in black tea, tea infusion and spent tea was studied. Analysis was carried out using high performance liquid chromatography with diode array detection. The rate of dissipation was found to vary with the nature of the substrate. In tea leaves the half-life of fenpyroximate ranged from 2.20 to 4.22 days. The residue of fenpyroximate was not detectable in the tea brew.